ANALISIS KEUNGGULAN BERSAING PERUSAHAAN BERDASARKAN RESOURCES BASED VIEW Studi Kasus PT Pamapersada Nusantara - , Yuni Budi Hastuti, Drs. Ahmad Jamli, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
PT. Pamapersada Nusantara (PAMA) is a coal mining contractor, after the issuance of Act 4 of 2009 on Mineral and Coal Mining (Mining Law) turn the investment climate in the coal industry. These conditions resulted in intense competition among mining business and increasing performance demands of its customers. Faced with this phenomenon the company must ensure that the business strategy is selected according to the environmental conditions and the company's business so it can grow and sustainable. Conditions of increasing competition requires companies to have a competitive advantage. Increasingly turbulent external environment makes coal mining company contest the new sources of competitive advantage, difficult to imitate, rare and valuable. The authors analyze the competitive conditions in the coal mining contractor company and positions of PT Pamapersada Nusantara against itâs competitors and what resources also capabilities of the company in order to be a competitive advantage. This research uses descriptive qualitative method by using CR4 and Herfindahl Hirschman Index to analyze the concentration ratio and using the calculation of the Minimum Efficient Scale (MES) to measure market entry barriers. As for the testing resources and capabilities owned by PT Pamapersada Nusantara, the authors use VRINE test (valuable, rare, inimitable or nonsubstitable, and exploitable). The analysis that has been done, it is concluded that: PT Pamapersada Nusantara with the resources and capabilities of its (heavy equipment, financial performance, human resources and knowledge, reputation and relationships, technology and innovation) are able to achieve sustained competitive advantage. With the resources and capabilities of its Pamapersada to compete and become the market leader among the competitors while minimizing business risk.